Fundamental Factor Analysis on Stock Returns Based on the Panel Data of LQ'45 Index - Sumani Sumani (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
This study aims to investigate the influence of fundamental factors on stock returns on the companies listed in the LQ’45 index in the Indonesia Stock Exchange. This research uses explanatory research design. The population consists of 45 companies listed in the LQ'45 index. The purposive sampling technique is used and collected a total of 23 companies as the sample. The number of samples was 23 companies because these companies consistently formed the LQ'45 index for the 2014-2018 periods. Those companies are fulfilling the criteria which are continually included in the LQ’45 index throughout the analysis period. Thus, the data panels used in this study were as much as 115 observations. Fundamental factors proxies by TATO, MBV, CR, DER, NPM, and EPS. The multiple linear regression analysis is used and the results showed that TATO has a significant positive effect on stock returns, MBV has a significant negative effect on stock returns, while CR, DER, NPM, and EPS have no significant effects on the stock return of LQ’45 index-listed companies.